Optimalisasi Patroli Tim Prabu Polrestabes Bandung Dalam Menekan Angka Tindak Pidana Curas Guna Terpeliharanya Situasi Kamtibmas - Beste, Beste Refo Kandida (Advances in Police Science Research Journal, 2019)
The criminal act of theft with violence is highly occurred in Indonesia. The criminal act of theft with violence was regulated under Article 365 of Indonesia Criminal Code. The police had carried out special patrol activity by the Prabu Team under the jurisdiction of Polrestabes Bandung which has functions to prevent the integration of the intention and opportunity factor in order to prevent or minimize the criminal act of theft with violence to maintain lawful environment and attempt to cultivate security and public order. This research aims to understand the general idea of the criminal act of theft with violence, to know each factors that influenced the rate of the criminal act of theft with violence, as well as to apprehend the optimization of the Prabu Team patrol activity to suppress the criminal rate of the theft with violence to maintain the security and public order. This research was conducted using qualitative method with analytical descriptive technique. The research location is under the jurisdiction of Polrestabes Bandung. All the data was collected using observation, interview and document study method. The validity of the data used triangulation source, technique, and time. The data was analyzed using data reduction, data presentation, and then drawing conclusions. This research shows that the rate of the criminal act of theft with violence at Bandung in 2019 has increased, compared to 2018. The act of theft using violence in 2019 jump from 191 cases to 201 cases. Time and zonation of theft with violence consists of certain areas and time, which is 27 spots and starts at 18:00-05:00 WIB. This research has obstacles that was caused by various inhibiting factors that restrains the Prabu Team’s performance.